Phenethyl Isothiocyanate Suppresses the Proinflammatory Cytokines in Human Glioblastoma Cells through the PI3K/Akt/NF-κB Signaling Pathway In Vitro. (25th March 2022) - Hsu, Sheng-Yao; Lee, Shih-Chieh; Liu, Hsin-Chung; Peng, Shu-Fen; Chueh, Fu-Shin; Lu, Tai-Jung; Lee, Hsu-Tung; Chou, Yu-Cheng
Abstract : Phenethyl isothiocyanate (PEITC), extracted from cruciferous vegetables, showed anticancer activity in many human cancer cells. Our previous studies disclosed the anticancer activity of PEITC in human glioblastoma multiforme (GBM) 8401 cells, including suppressing the cell proliferation, inducing apoptotic cell death, and suppressing cell migration and invasion. Furthermore, PEITC also inhibited the growth of xenograft tumors of human glioblastoma cells. We are the first to investigate PEITC effects on the receptor tyrosine kinase (RTK) signaling pathway and the effects of proinflammatory cytokines on glioblastoma. The cell viability was analyzed by flow cytometric assay. The protein levels and mRNA expressions of cytokines, including tumor necrosis factor- α (TNF- α ), interleukin-1 β (IL-1 β ), and interleukin-6 (IL-6), were determined by enzyme-linked immunosorbent assay (ELISA) reader and real-time polymerase chain reaction (PCR) analysis, respectively. Furthermore, nuclear factor-kappa B- (NF- κ B-) associated proteins were evaluated by western blotting. NF- κ B expression and nuclear translocation were confirmed by confocal laser microscopy. NF- κ B binding to the DNA was examined by electrophoretic mobility shift assay (EMSA). Our results indicated that PEITC decreased the cell viability and inhibited the protein levels and expressions of IL-1 β, IL-6, and TNF- α genes at the transcriptional level in GBM 8401 cells. PEITC inhibited the binding of NF- κ B on promoter site of DNA in GBM 8401 cells. PEITC also altered the protein expressions of protein kinase B (Akt), extracellular signal-regulated kinase (ERK), and NF- κ B signaling pathways. The inflammatory responses in human glioblastoma cells may be suppressed by PEITC through the phosphoinositide 3-kinase (PI3K)/Akt/NF- κ B signaling pathway. Thus, PEITC may have the potential to be an anti-inflammatory agent for human glioblastoma in the future.